Preventive field application of Metarhizium brunneum in cover crops for wireworm control. (December 2021) - Reinbacher, Lara; Bacher, Sven; Knecht, Fionna; Schweizer, Christian; Sostizzo, Tanja; Grabenweger, Giselher
Abstract: Wireworms, the larvae of click beetles (Coleoptera: Elateridae), can cause substantial losses in marketable yield of potatoes, yet control options are limited. The entomopathogenic fungus Metarhizium brunneum (Ascomycota; Hypocreales) isolate ART2825 is highly virulent against two of the most detrimental wireworm species, Agriotes obscurus L . and A. lineatus L ., but field application of this isolate during potato cultivation has never succeeded. In this study, we integrated the fungus into the agricultural crop rotation prior to potato cultivation, with the aim of better adapting the application strategy to the fungus' ecological and environmental requirements. Application preceded sowing of cover crops in late summer. We hypothesized that higher temperatures and undisturbed development for several months would support the establishment of the entomopathogen and enhance biocontrol efficiency in the following season. In two subsequent seasons, we quantified (1) fungal establishment in the soil, (2) efficiency of treated soils against wireworms in vitro, and (3) levels of wireworm damage in field potatoes. Spore concentration was enhanced in treated plots and we recovered the released Metarhizium isolate from all mycosed, field-collected wireworms. Treated soils increased wireworm mortality in the laboratory, but a statistically significant reduction of potato damage was only achieved in two out of ten field trials. The application strategy shows potential for fungal enhancement and opens new avenues for biological wireworm control. Highlights: Application enhanced fungus in soil over entire cover crop growing period. Treated soils increased wireworm mortality in vitro. Released Metarhizium isolate was recovered from field-collected wireworms. Reduced damage in potato but effect needs to be improved for practical use. Study highlights necessity of further wireworm research.